ANALISIS FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN LAPORAN PERUSAHAAN BERBASIS WEBSITE - Deko Anggoro Akbar; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
The purpose of this study is to analyze the effect of firm size, profitability, leverage, auditor size, public ownership, ICT industry and new shares offering on the level of disclosure web-based reporting in Indonesian company’s. The samples used in this study were 77 non-financial companies listed on the Indonesia Stock Exchange in 2013. With proportional stratified random sampling method, the sample firms are grouped according to the type of industry. Data used in this study is a secondary data, the annual reports of listed companies in Indonesia Stock Exchange in 2013 and observations on the company's website. The analytical method used is multiple linear regression. The conclusion that can be drawn from this study is the variable firm size, profitability and ICT industry significant and positive impact on the level of disclosure based on the company's website in Indonesia, while the other variables are not shown to have a significant effect.